Can You Help Someone Become Financially Capable? A Meta-Analysis of the Literature - Miller, Margaret; Reichelstein, Julia; Salas, Christian; Zia, Bilal (World Bank, Washington, DC, 2014)
This paper presents a systematic and comprehensive meta-analysis of the literature on financial education interventions. The analysis focuses on financial education studies designed to strengthen the financial knowledge and behaviors of consumers. The analysis identifies 188 papers and articles that present impact results of interventions designed to increase consumers' financial knowledge (financial literacy) or skills, attitudes, and behaviors (financial capability). These papers are diverse across a number of dimensions, including objectives of the program intervention, expected outcomes, intensity and duration of the intervention, delivery channel used, and type of population targeted. However, there are a few key outcome indicators where a subset of papers are comparable, including those that address savings behavior, defaults on loans, and financial skills, such as record keeping. The results from the meta analysis indicate that financial literacy and capability interventions can have a positive impact in some areas (increasing savings and promoting financial skills such as record keeping) but not in others (credit default).